Education and Mentoring Pocket Money Management for Students of BHS Islamic Boarding Schools - Amin, Muh. Sirojuddin; Primanto, Alfian Budi (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
Pocket money is an essential thing in the lives of Islamic boarding school students. The students use pocket money not only for basic needs but also for other things. However, in its use, it often needs to catch up to the target. This causes Islamic boarding school students to frequently need more pocket money before their parents send more money. With these problems, this community service activity focuses on being more effective and efficient in using pocket money. Using a control card system that makes it easier for students to know how to use their pocket money will also make it easier to plan their finances in the future. This control card can be adapted to the needs of each Islamic boarding school and can be accessed by both parties, students and parents. By implementing these steps, Islamic boarding school students' use of pocket money can be more effective and efficient.